(untitled) (Journal of Plant Disease Sciences, 2023)
Morphological variability among the isolates of Colletotrichum capsici causing leaf spot of turmeric was assessed in laboratory condition. The infected leaf samples were collected from different locations. Pathogenicity of the pathogen was proved on inoculated plants of turmeric and the re-isolation from artificially diseased plants tissues on PDA consistently yielded C. capsici, thus confirmed the Koch’s postulates. Morphological characters of five different isolates with respect to mean colony diameter, colony appearance, conidial characters, presence of setae and acervuli were studied on PDA. Isolates Cc-1 to Cc-5 exhibited colony colour from white to black, pinkish to dark black, black to ash and grey to white and possesses concentric rings except Cc-3 and Cc-4 which possesses irregular shapes. Conidia of all isolates were sickle shaped having oil globule at the centre and Cc-5 possesses micro sickle shaped conidia having oil globule at the centre. Acervuli with setae were present in all isolates while in Cc-5 acervuli with setae were not observed. Acervuli are black to brown in colour and setae were longer than conidial mass in all the isolates. Maximum mean colony diameter of 85 and 82 mm was recorded in Cc-4 and Cc-2 respectively, whereas minimum growth 75 mm was recorded in Cc-5 at 10 days after inoculation (DAI).